The Effect of Corporate Governance, Green Accounting and Leverage on Company Profitability on Pefindo I-Grade Index - Setiadi, Abigail Dwi Pangestu; Hutabarat, Francis M.; Sinaga, Judith T. Gallena (Ilomata International Journal of Tax and Accounting, 2024)
Profitability plays an important role in reflecting a company's performance in generating profits. Therefore, this study was conducted to demonstrate the effects of corporate governance, green accounting, and leverage on company profitability. This study utilizes a quantitative approach with secondary data. The research population comprises companies listed on the Pefindo I-Grade Index. The sample size is 30 companies over a 5-year period, resulting in 150 samples. Over a period of five years, data was collected from various companies, resulting in a total of 150 samples. A regression analysis was conducted, and the findings from this test indicate that corporate governance and green accounting do not have impact on company profitability, whereas the leverage ratio has a negative and significant effect on company profitability.